The Consequences of the Six Day War for the Jewish Communities of Arab countries from Hungarian Perspective - Abdallah, Abdel-Ati Al-Naggar; Prantner, Zoltán (Études sur la Région Méditerranéenne, 2023)
Jews living in Arab countries faced discrimination even before 1967, namely after the establishment of a territorial Jewish State in 1948. However, the Six-Day War brought them further suffering, which often had a serious impact on the existence of Israelite communities dating back to ancient times. The significant reduction in the size of some Jewish communities in the Arab world depended largely on the policies of their ‘mother state’. Thus, Jewish emigration was less decisive in Maghreb countries, where governments sought to protect their Jewish citizens from atrocities fuelled by anti-Jewish and anti- Semitic sentiments.1 The situation was quite different in the Middle Eastern states, where governments themselves were often responsible for some incidents against Jews. The Hungarian Foreign Ministry also tried to follow all these events, but due to the political and interstate relations of the time, it did not always manage to form a realistic image of them.